French Energy Sector in Search for Optimal Model - A. V. Zimakov (Vestnik MGIMO-Universiteta)
Clean energy transition is one of major transformation processes in the EU. There are different approaches among EU countries to decarbonization of their energy systems. The article deals with clean energy transition in France with the emphasis on power generation. While this transformation process is in line with similar developments in the EU, the Franch case has its distinct nature due to nuclear power domination in electricity production there. It represents a challenge for the current model as the transition is linked to a sharp drop of nuclear share in the power mix. It is important to understand the trajectory of further clean energy transition in France and its ultimate model. The article reviews the historical roots of the current model (which stems from Messmer plan of the 1970-es) and its development over years, as well as assesses its drawbacks and merits in order to outline possible future prospects. The conclusion is that the desired reduction of nuclear energy is linked not solely to greening process but has a complex of reasons, the ageing of nuclear reactors being one of them. Nuclear power remains an important low-carbon technology allowing France to achieve carbon neutrality by 2050. A desired future energy model in France can be understood based on the analysis of new legislation and government action plans. The targeted model is expected to balance of nuclear and green energy in the generation mix in 50% to 40% proportion by 2035, with the rest left to gas power generation. Being pragmatic, French government aims at partial nuclear reactors shut down provided that this will not lead to the rise of GHG emissions, energy market distortions, or electricity price hikes. The balanced French model is believed to be a softer and socially comfortable option of low-carbon model.